2009
DOI: 10.2754/avb200978030471
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc, Iron and Copper Concentrations in Dogs Infected with Hepatozoon canis

Abstract: In Turkey, canine hepatozoonosis is an emerging infection with a large number of cases detected during the past five years. In the present study, serum zinc, copper and iron concentrations of dogs infected with Hepatozoon canis were measured for the first time. Compared to the controls (n = 10), serum zinc and iron concentrations in infected animals (n = 14) decreased significantly (p < 0.05 and p < 0.01, respectively), whereas the concentrations of copper in diseased animals increased significantly (p < 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…Furthermore, our recorded corroborate the opinion of (32) who reported that Hepatozoon canis caused an increased in serum Cu level and a decreased in Zn level. Contrary to our results, Seyrek et al (32) mentioned that serum Fe decreased in dog infected with H. canis. Many factors have been explained to reduce the level of Zn in the serum of animal including indirect effect of the host-parasite relationship or increased Zn demand by the parasite itself (33), and hormonal changes (34).…”
Section: Trace Elements Estimationcontrasting
confidence: 99%
“…Furthermore, our recorded corroborate the opinion of (32) who reported that Hepatozoon canis caused an increased in serum Cu level and a decreased in Zn level. Contrary to our results, Seyrek et al (32) mentioned that serum Fe decreased in dog infected with H. canis. Many factors have been explained to reduce the level of Zn in the serum of animal including indirect effect of the host-parasite relationship or increased Zn demand by the parasite itself (33), and hormonal changes (34).…”
Section: Trace Elements Estimationcontrasting
confidence: 99%
“…Serum copper concentrations are also higher in human patients suffering from hepatic disorders [ 31 ], and elevated Cu:Zn ratios have been proposed as markers of disease in patients with hepatic cirrhosis [ 31 ] or hepatocellular carcinoma [ 32 ]. The role of Cu in the acute-phase protein ceruloplasmin in controlling acute inflammatory-infectious disorders, leading to a marked increase in Cu serum concentrations, is well known in both dogs [ 22 , 33 ] and humans [ 34 ]. There is evidence of increased concentrations of Cu and decreased concentrations of Fe and Zn in serum of dogs infected with Hepatozoon canis [ 22 ] and with Rangelia vitalii (Apicomplexa: Piroplasmorida) [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of Cu in the acute-phase protein ceruloplasmin in controlling acute inflammatory-infectious disorders, leading to a marked increase in Cu serum concentrations, is well known in both dogs [ 22 , 33 ] and humans [ 34 ]. There is evidence of increased concentrations of Cu and decreased concentrations of Fe and Zn in serum of dogs infected with Hepatozoon canis [ 22 ] and with Rangelia vitalii (Apicomplexa: Piroplasmorida) [ 33 ]. The concentrations of Cu in human serum are increased in various carcinomas [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the author's knowledge, report on the levels of these minerals in dogs with CME or any other rickettsial disease is lacking to compare the present findings. However, low levels of Zn and Cu have been reported in case of other tick-borne diseases like Babesia gibsoni [42] and Hepatozoon canis [43] in dogs.…”
Section: Plasma Hormonal and Blood Mineral Profile Of Affected Animalsmentioning
confidence: 99%